Optimization of vitamins A and D3 loading in re-assembled casein micelles and effect of loading on stability of vitamin D3 during storage. (1st February 2018) - Loewen, Anisa; Chan, Benny; Li-Chan, Eunice C.Y.
Highlights: Vitamins A and D could be loaded into re-assembled casein micelles. Vitamin loading was optimized by altering phosphate, citrate and calcium levels. Loading into re-assembled casein micelles improved stability of vitamin D powders during storage. Abstract: The objectives of this study were to apply response surface methodology to optimize fat-soluble vitamin loading in re-assembled casein micelles, and to evaluate vitamin D stability of dry formulations during ambient or accelerated storage and in fortified fluid skim milk stored under refrigeration. Optimal loading of vitamin A (1.46–1.48 mg/100 mg casein) was found at 9.7 mM phosphate, 5.5 mM citrate and 30.0 mM calcium, while optimal loading of vitamin D (1.38–1.46 mg/100 mg casein) was found at 4.9 mM phosphate, 4.0 mM citrate and 26.1 mM calcium. In general, more vitamin D was retained in vitamin D-re-assembled casein micelles than control powders during storage, while vitamin D loss was not different for vitamin D-re-assembled casein micelles and control fortified milks after 21 days of refrigerated storage with light exposure. In conclusion, re-assembled casein micelles with high loading efficiency show promise for improving vitamin D stability during dry storage.